Review on Early Ovarian Carcinoma using Radiomics - Sheela, SN; Chandrappa, DN (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Ovarian cancer remains one of the deadliest gynecological malignancies in the world, despite major advances in chemotherapy and surgery. This, according to several research, is related to the considerable heterogeneity in treatment response and prognosis. Mostly, computational approaches for assessing tumour heterogeneity have been developed, which employ medical imaging and radio genomes to look at the whole tumour heterogeneity rather than just a single biopsy sample. This tumoral heterogeneity is not taken into consideration by standard imaging utilising CT or MRI, especially in late stages of peritoneal carcinomatosis. As a result, medical imaging has been recommended as a new field in the assessment of tumour heterogeneity, rather than single biopsy sample, to evaluate the entire tumour burden heterogeneity. In medical imaging there are four basic steps involved for an efficient and accurate detection of ovarian cancer at early stage. This review discusses about the detail evaluation on the various four phases involved in Medical imaging. Thus the review brings out a detail evaluation of Medical imaging undertaken at every stage of processing. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(1): 39-46